Exploring the effect of aliovalent substitution of Pb2+ by Eu3+ on structural, morphological and optical properties of CH3NH3PbI3 perovskite films. (12th February 2020) - Derbali, S; Nouneh, K; Florea, M; Neatu, F; Neatu, S; Leonat, L N; Secu, M; Tomulescu, A G; Stancu, V; Pintilie, L; Touhami, M Ebn; Galca, A C
Abstract: In this work, the effect of aliovalent substitution of Pb 2+ by Eu 3+ on structural, morphological and optical properties of CH3 NH3 PbI3 (MAPbI3 ) was studied, aiming to improve the properties of perovskite films used in solar cells application. The surface morphology, the microstructure and the optical properties of the obtained films containing different Europium (Eu) concentrations were characterized by atomic force microscopy, x-ray photoelectron spectroscopy, x-ray diffraction, UV–vis spectroscopy and photoluminescence spectroscopy.